Three dimensional band-filling control of complex oxides triggered by interfacial electron transfer - Meng Meng (Nature Portfolio, 2021)
Band-filling control of transition metal ions in oxide heterostructures is typically limited to the two-dimensional interface. Here, the authors report a three-dimensional modulation of the band-filling and a topotactic phase transition in LaCoO3, triggered by charge transfer at LaCoO3/LaTiO3 interface.